EFFECT ANALYSIS OF EXPORTS, IMPORTS, AND MANUFACTURING ON INDONESIA'S GDP FROM 1990 TO 2019 - Saputri, Ardianti Suci; Sasana, Hadi (Transpublika Publisher, 2022)
This study's primary purpose is to determine and assess the impact of exports, imports, and manufacturing in Indonesia from 1990 to 2019. The secondary data utilized by the researcher in this study spans the years 1990 to 2019. Imports and exports of commodities and services in the 1990s, when there was no import-export ease, compared to 1998, when Indonesia had import-export ease. The issue was that a monetary crisis caused Indonesia's economic structure to become somewhat disorganized, as the rupiah exchange rate and inflation rose, and enterprises with foreign debts were compelled to repay them in multiples of their original sums. In this study, researchers conducted tests using the eviwes 10 application and the ECM (Error Correction Model) approach, with data on the growth rate of exports, imports, and economic growth obtained from the World Bank from 1990 to 2019. The data acquired in the form of numbers that are analyzed and display the status of being stationary. Exports are stationary with a probability of 0.0000, where the value is less than 5%, imports are stationary with a probability of 0.0011, where the value is less than 5%, and manufacturing is stationary with a probability of 0.0021, where the value is < 5%, and GDP or economic growth is 0.0147, which is less than 5%.